2022
DOI: 10.1101/2022.11.01.514706
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Transport and utilization of glycogen breakdown products byGardnerellaspp. from the human vaginal microbiome

Abstract: MultipleGardnerellaspecies frequently co-occur in vaginal microbiomes, and several factors including competition for nutrients such as glycogen could determine their population structure. AlthoughGardnerellaspp. can hydrolyze glycogen to produce glucose, maltose, maltotriose and maltotetraose, how these sugars are transported and utilized for growth is unknown. We determined the distribution of genes encoding transporter proteins associated with the uptake of glucose, maltose, and malto-oligosaccharides and ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…The larger breakdown products of glycogen digestion (maltose, maltotriose, maltotetraose, malto-oligosaccharides) and extracellular glucose are taken up by two distinct types of transport systems. Products of glycogen digestion are transported into lactobacilli through the four component ATP-binding cassette transport system MalEFG/MsmK [ 73 , 74 ] while G. vaginalis has four separate transport systems for these products: the MusEFGK2I operon (maltose/maltotriose), the MalXFGK transporter (maltose, maltotriose, malto-oligosaccharides and maltodextrins), RafEFGK (α-1,6 linked glucosides and galactosides), and TMSP 322 (trehalose/maltose) [ 75 ]. Similar to E. coli and other bacteria, glucose can be transported into L. jensenii , L. gasseri and L. crispatus by the phosphoenolpyruvate: carbohydrate phosphotransferase system [ 76 , 77 ] and into G. vaginalis by a putative glucose/galactose porter [ 75 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The larger breakdown products of glycogen digestion (maltose, maltotriose, maltotetraose, malto-oligosaccharides) and extracellular glucose are taken up by two distinct types of transport systems. Products of glycogen digestion are transported into lactobacilli through the four component ATP-binding cassette transport system MalEFG/MsmK [ 73 , 74 ] while G. vaginalis has four separate transport systems for these products: the MusEFGK2I operon (maltose/maltotriose), the MalXFGK transporter (maltose, maltotriose, malto-oligosaccharides and maltodextrins), RafEFGK (α-1,6 linked glucosides and galactosides), and TMSP 322 (trehalose/maltose) [ 75 ]. Similar to E. coli and other bacteria, glucose can be transported into L. jensenii , L. gasseri and L. crispatus by the phosphoenolpyruvate: carbohydrate phosphotransferase system [ 76 , 77 ] and into G. vaginalis by a putative glucose/galactose porter [ 75 ].…”
Section: Discussionmentioning
confidence: 99%
“…Products of glycogen digestion are transported into lactobacilli through the four component ATP-binding cassette transport system MalEFG/MsmK [ 73 , 74 ] while G. vaginalis has four separate transport systems for these products: the MusEFGK2I operon (maltose/maltotriose), the MalXFGK transporter (maltose, maltotriose, malto-oligosaccharides and maltodextrins), RafEFGK (α-1,6 linked glucosides and galactosides), and TMSP 322 (trehalose/maltose) [ 75 ]. Similar to E. coli and other bacteria, glucose can be transported into L. jensenii , L. gasseri and L. crispatus by the phosphoenolpyruvate: carbohydrate phosphotransferase system [ 76 , 77 ] and into G. vaginalis by a putative glucose/galactose porter [ 75 ]. As with the glycogen utilization proteins, i n silico analysis revealed presence of transportation systems for glycogen breakdown products in our tested strains (Table S2 ).…”
Section: Discussionmentioning
confidence: 99%
“…A heterologously expressed homologue of this enzyme in Gardnerella was found to degrade amylose, pullulan, glycogen and starch (23). Recent research showed that 14 out of 15 tested Gardnerella strains carried a full copy of this gene (17) and that isolates of four different Gardnerella species can transport and metabolize the small maltodextrins derived from glycogen breakdown (24).…”
Section: Introductionmentioning
confidence: 99%